Organic Animal Waste as a Growth Substrate for Metarhizium anisopliae: A Viability Analysis - Sucipto, Irwanto; Muhlison, Wildan; Anggarini, Cindy Dwi; Safitri, Eva; Tanzil, Ahmad Ilham (Universitas Muhammadiyah Jember, 2025)
Entomopathogenic fungi are important biological control agents and also have a good impact on the environment. One of the many entomopathogenic fungi that is safe for use by humans is Metarhizium anisopliae. Besides being parasitic, this type of fungus is also saprophytic in that this fungus utilizes organic matter as food. The organic material used will later become the media or substrate for the propagation of Metarhizium anisopliae. The substrate used is usually PDA (Potatoe Dextrose Agar), but due to the high price, farmers usually try to use other organic materials which are more affordable, and what is often used is corn rice. However, until now it has not been confirmed which substrate is the best for Metarhizium anisopliae. Therefore this study aims to determine the viability of entomopathogenic fungi on organic fertilizer substrates. Analysis of the research parameters was carried out at the Agrotechnology Laboratory, Faculty of Agriculture, University of Jember. The study design used a completely randomized design (CRD) with 5 treatments and 5 repetitions, so there were 25 sample units, with observations for 8 weeks so that the total number of samples was 200 samples. The treatments used included P0: using corn-rice media, P1: using chicken manure media, P2: using cow manure media, P3: using goat manure media, P4: using bat manure media. The research variables used were incubation period, final sample weight, and conidia density. The aim of this study was to determine the most suitable substrate for the growth and effectiveness of Metarhizium anisopliae as a biological control agent. The best-performing media were found to be chicken manure and cow manure. The authors suggest further emphasis on the scientific contribution of this research and recommend these substrates for practical field application